Pandemi Covid-19 Sebagai Peristiwa Dunia: Analisis Teologi Profetik Kitab Yoel 1-2 Terhadap Krisis Global Kontemporer - La'ia, Dewi (JOURNAL of THEOLOGICAL STUDENTS, 2025)
This study analyzes contemporary natural events through the theological perspective of the Book of Joel 1-2, particularly the concept of the "Day of the Lord," which encompasses judgment, salvation, and the restoration of the people. Using the grammatical-historical exegesis method and contextual-theological hermeneutics, this study identifies a theological pattern of crisis-repentance-restoration in Joel's locust plague narrative and applies it to the context of the COVID-19 pandemic. The study finds that God delivers warnings in two ways: sending His servants and using natural disasters as instruments of judgment. The research findings indicate a structural parallel between the locust plague (Joel 1:4-12) and the impact of the COVID-19 pandemic: both result in ecological-economic crises, disruptions of religious rituals, and social disintegration. The uniqueness of this study lies in its theological interpretation that connects ancient texts with contemporary global crises, showing the relevance of Joel's prophetic message in the modern era. COVID-19, Like a locust plague, it serves as a warning for humans to recognize their dependence on God, to care for His creation, and to renew their spiritual relationship.